A Catalogue and Historical Study of the Odonata of Ecuador - Mauffray, William F.; Tennessen, Kenneth J. (Zootaxa, 2019)
We present a list of 425 valid Odonata species from Ecuador, providing a brief overview of each genus, a photograph of a representative species of each genus, and all records known to us for each species. Thirty-eight of the 425 species were previously unrecorded from Ecuador. Data were derived from published records, public and private collections, and field records accumulated since the 1960’s by the authors and others who have contributed specimen information to this study. A historical study and a comprehensive list of synonyms are presented, and questionable species records are discussed. The physiography of the country, including the general climate of each subregion and current pressures on the environment, is briefly discussed. At present, 44 species of Odonata are considered endemic to Ecuador, and eight species are considered endangered, vulnerable, or near threatened on the IUCN Red List.